2018
DOI: 10.1007/s10995-018-02694-0
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Healthcare Use and Child Morbidity 4 Years After User Fee Removal in Rural Burkina Faso

Abstract: Objectives Increasing financial access to healthcare is proposed to being essential for improving child health outcomes, but the available evidence on the relationship between increased access and health remains scarce. Four years after its launch, we evaluated the contextual effect of user fee removal intervention on the probability of an illness occurring and the likelihood of using health services among children under 5. We also explored the potential effect on the inequality in healthcare access… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
(76 reference statements)
0
6
0
Order By: Relevance
“…This appears to concur with a rigorous mapping exercise at the country level which revealed that many nutrition-specific interventions had satisfactory geographical coverage in 2014 (Doudou et al, 2018 ). Free healthcare to pregnant women and children under five was largely cited by community members as a very recent driver of tangible improvement, and has proven to lead to a significant 17% increase in the use of health services in the longer term (Zombré et al, 2019 ). Finally, family planning programs that aim at optimizing age at first pregnancy, family size and inter-pregnancy intervals, lead to better health and nutrition pregnancy outcomes (Bhutta et al, 2013 ); There is currently a large, though declining, unmet need for contraceptives in Burkina Faso, especially for spacing births (Institut Supérieur des Sciences de la Population, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…This appears to concur with a rigorous mapping exercise at the country level which revealed that many nutrition-specific interventions had satisfactory geographical coverage in 2014 (Doudou et al, 2018 ). Free healthcare to pregnant women and children under five was largely cited by community members as a very recent driver of tangible improvement, and has proven to lead to a significant 17% increase in the use of health services in the longer term (Zombré et al, 2019 ). Finally, family planning programs that aim at optimizing age at first pregnancy, family size and inter-pregnancy intervals, lead to better health and nutrition pregnancy outcomes (Bhutta et al, 2013 ); There is currently a large, though declining, unmet need for contraceptives in Burkina Faso, especially for spacing births (Institut Supérieur des Sciences de la Population, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…This low-income country has an estimated gross domestic product of 786.895 US dollars, and approximately 40.1% of the entire population lives below the poverty threshold [22]. Children under 5 years of age represent 18% of the entire population, and more than 1 out of every 9 children die before the age of 5 years from preventable febrile illnesses such as malaria, pneumonia and diarrhoeal infections [19,23]. Moreover only 50% of children have access to formal healthcare in Burkina Faso [19].…”
Section: Settingmentioning
confidence: 99%
“…Children under 5 years of age represent 18% of the entire population, and more than 1 out of every 9 children die before the age of 5 years from preventable febrile illnesses such as malaria, pneumonia and diarrhoeal infections [19,23]. Moreover only 50% of children have access to formal healthcare in Burkina Faso [19].…”
Section: Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence of effects is mixed, and a previous analysis of the reform in Zambia looking at the effect of the policy 1-year post reform showed no change in facility-based deliveries ( Chama-Chiliba & Koch, 2016 ). With the exception of Burkina Faso, where Zombré, De Allegri et al (2019) analysed the effect at four years, there is hardly any evidence on the effects of free care once the policy has matured, even though beneficial effects may take time to appear due to teething problems to implement the policy effectively in the short-term or slow behavioural change ( Carasso, Lagarde et al, 2012 ). As a result, the null effects observed in studies evaluating the short-term effects of policy change can either be explained by a true lack of effectiveness of user fee removal or the challenges associated with the introduction of the policy.…”
Section: Introductionmentioning
confidence: 99%